2014
DOI: 10.1038/eye.2014.130
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic diabetic retinopathy as a possible prognostic factor for chronic kidney disease progression

Abstract: Purpose To assess the value of diabetic retinopathy (DR) severity as a possible predictive prognostic factor for the progression of chronic kidney disease (CKD). Patients and methods Retrospective cohort study. Patients (51) who were initially diagnosed with DR and CKD were enrolled and their medical records were evaluated. The following ophthalmic factors were assessed by fluorescein angiography at the initial visit: area of capillary nonperfusion, presence of neovascularization and vitreous hemorrhage, and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 20 publications
2
28
0
Order By: Relevance
“…13 On the other hand, one study demonstrated that a more extensive nonperfusion area in the retina increased the risk of progression of CKD over a 2-year period. 14 These studies strengthened the link between diabetic retinopathy and nephropathy, suggesting that either one may progress along with the other. Chronic kidney disease has been implicated in the production of vascular endothelial growth factors (VEGF) that are normally detected in podocytes in glomeruli and tubular epithelial cells.…”
Section: Discussionmentioning
confidence: 80%
“…13 On the other hand, one study demonstrated that a more extensive nonperfusion area in the retina increased the risk of progression of CKD over a 2-year period. 14 These studies strengthened the link between diabetic retinopathy and nephropathy, suggesting that either one may progress along with the other. Chronic kidney disease has been implicated in the production of vascular endothelial growth factors (VEGF) that are normally detected in podocytes in glomeruli and tubular epithelial cells.…”
Section: Discussionmentioning
confidence: 80%
“…Few studies have demonstrated that CKD is associated with DR and it is not clear if CKD in the absence of albuminuria is associated with DR. [47][48][49] Sabanayagam et al 47 demonstrated that CKD is associated with DR only in the presence of albuminuria, suggesting that CKD is more likely related to diabetes in the presence of albuminuria. Lee et al 48 demonstrated that ischemic DR characterized with extensive capillary nonperfusion is a possible prognostic factor for the progression of CKD. Additional studies are needed to explore the relationship between DR and CKD further.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, Lee et al [ 31 ] showed a direct association between DR and CKD. The presence of CKD identified a group of DM2 patients of being at a greater risk of presenting macro and microvascular complications.…”
Section: Discussionmentioning
confidence: 99%